2015
DOI: 10.1017/s0030605315000174
|View full text |Cite
|
Sign up to set email alerts
|

Participatory forest carbon assessment in south-eastern Tanzania: experiences, costs and implications for REDD+ initiatives

Abstract: The aim of this study was to determine the changes in forest carbon in three village forests in Tanzania during - using participatory forest carbon assessment, and to evaluate the capability of the local communities to undertake the assessment, and the costs involved. The results show that forest degradation is caused not only by disturbance as a result of anthropogenic activities; other causes include natural mortality of small trees as a result of canopy closure, and the attraction of wild animals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…The impact of fire on a landscape depends on the timing and frequency of burning and on the availability of inflammable biomass. Complete protection of a forest for a number of years leads to an accumulation of fuel, which is more detrimental to tree biomass if a fire occurs; thus a fire management regime is necessary for the forest to thrive (Katani et al, 2015). The REDD+ project of the Mpingo Conservation and Development Initiative, which combines participatory forest management efforts with a fire management plan, can potentially generate lasting changes, with positive effects such as increased income and improved governance (Khatun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of fire on a landscape depends on the timing and frequency of burning and on the availability of inflammable biomass. Complete protection of a forest for a number of years leads to an accumulation of fuel, which is more detrimental to tree biomass if a fire occurs; thus a fire management regime is necessary for the forest to thrive (Katani et al, 2015). The REDD+ project of the Mpingo Conservation and Development Initiative, which combines participatory forest management efforts with a fire management plan, can potentially generate lasting changes, with positive effects such as increased income and improved governance (Khatun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Most women interviewed lacked even basic knowledge of REDD+ activities unless they were involved in the relevant committee. Effective participation is necessary to ensure that REDD+ contributes to income diversification in communities (Katani et al, 2015), and therefore a more structured approach to early burning, with well-publicized advance planning and targeting all community members, could make a significant difference for both ethical and practical reasons: ethical because people need to understand that early burning activities serve both ecological and carbon trading purposes, and practical because poor understanding of carbon offsetting can lead to misunderstandings if carbon savings are ever realized and commercialized. Communities vary structurally and socially, and project managers need to target their efforts in awareness raising and training appropriately to ensure the broadest participation in both participatory forest management and REDD+ activities.…”
Section: Discussionmentioning
confidence: 99%
“…Til denne studien benyttet jeg sekundaere datakilder. Informasjon om utgifter og inntekter knyttet til jordbruksproduksjon, trekullproduksjon, priser på mais og trekull, karbontetthet, utbredelse av ulik arealbruk og tilvekst i Miombo ble hentet fra publisert litteratur (Hofstad, 1997, Hofstad & Sankhayan, 1999, Araya & Hofstad, 2014, Hofstad and Araya, 2015, Katani et al, 2016, Kessay et al, 2016.…”
Section: Dataunclassified
“…der PI er inventeringskostnader (0,66 USD ha -1 (Katani et al, 2016)), IM er transaksjonskostnader (1,2 USD ha -1 (Kessay et al, 2016)) og rr er prinsipalens realrente (rr=2%).…”
Section: Modelleringstilnaermingunclassified
“…For countries planning to implement UNFCCC policy on Reduced Emissions from Deforestation and forest degradation (REDD+), the economic and financial implications of mitigation options are important. Although the IPCC AR5 analysis of global and regional costs associated with REDD+ demonstrated that forestry-related emission mitigation as a whole represents a cost-effective instrument and produces institutional, economic, social, and environmental benefits in addition, there remain some unresolved fundamental issues regarding costs (Graham et al 2016, Palmer 2011, Leplay et al 2011, Ojea et al 2016, Katani et al 2016.…”
Section: Introductionmentioning
confidence: 99%